Thermal Analysis of Satellite Libertad 2: a Guide to CubeSat Temperature Prediction - Alejandro Garzón; Yovani A Villanueva (Journal of Aerospace Technology and Management, 2018)
We present a model for predicting the temperature of three-unit CubeSat on a low Earth orbit, which supposes a single temperature common to all satellite components. Our exposition includes a detailed, to a large extent analytical, computation of the external heat fluxes for a particular orbit and spacecraft assumptions based on the features foreseen for satellite Libertad 2 under development at Universidad Sergio Arboleda. Moreover, supported by specialized thermal analysis software, we compute the heat fluxes and their associated temperature for all possible orbital orientations, and combine these results with a description of the satellite orbital plane rotation (nodal regression) and the solar motion on the ecliptic, to determine the minima and maxima of the orbital temperature oscillation for a mission lifetime of a year. We find that, for feasible model parameters, the temperature extremes are mostly within the operating temperature range of the most sensitive satellite component, 0 °C ≤ T ≤ 60 °C, suggesting mission viability. Finally, we discuss possible model improvements which would allow testing of satellite design upgrades. In this regard, it is worth noting that the calculation of the external heat fluxes here described can be carried over, almost unchanged, to a more accurate model describing heat transfer between satellite parts with different temperatures.